PENGARUH KUALITAS PELAYANAN BANK SYARIAH MANDIRI PAYMENT POINT UNMUHA TERHADAP KEPUASAN MAHASISWA FAKULTAS EKONOMI UNIVERSITAS MUHAMMADIYAH ACEH - Kiki Putri Amelia; Hendri Mauliansyah (Asosiasi Dosen dan Praktisi Ekonomi Nusantara, 2024)
Bank Syariah Mandiri (BSM) Payment Point UNMUHA is an Islamic banking at the University of Muhammadiyah Aceh (UNMUHA) which is engaged in services, good service quality will be able to affect customer comfort. The purpose of the study was to determine the effect of service quality of BSM Payment Point UNMUHA on student satisfaction at the Faculty of Economics, UNMUHA. In this study, the population used was students of the Faculty of Economics UNMUHA as many as 1,381 people. The number of samples used was 93 people selected by Stratified Random Sampling. The data analysis tool used in this study is multiple linear regression analysis consisting of dependent variables and independent variables, for the dependent variable, namely student satisfaction (Y) while the independent variables are reliability (X1), responsiveness (X2), asssurance (X3), empathy (X4), and tangible (X5). The results showed that the effect of service quality of BSM Payment Point UNMUHA on the satisfaction of students of the Faculty of Economics UNMUHA for the dimension of service quality with the highest level of satisfaction is the dimension of responsiveness which is 2.920 and for the dimension of service quality with the lowest level of satisfaction is emphaty which is -1.315. Based on the results of this study, it can be seen that emphaty does not have an influence on customer satisfaction of BSM Payment Point UNMUHA with a coefficient value of -1.315. therefore it is hoped that the BSM Payment Point UNMUHA will be able to improve customer satisfaction.